Meningkatkan Kemampuan Kognitif Dengan Penerapan Metode Pembelajaran Berbasis Proyek Kegiatan Mengelompokkan Buah Jeruk - Sulistiani; Nurina (Jurnal Pendidikan Tuntas, 2023)
The learning proses in kindergarten is still very conventional in nature, This is shown is teaching an learning activites in kindergarden Taman Kanak kanak Bersemi kepenuhan jaya Rokan Hulu.in traducing the number of teacher skill using the lecture method and memorizing.To count number children still write in the book given by their teacher.The research is currenty doing is to improve numeracy skill in children aged 5-6 year with interesting activities for children by providing learning methods need for children .This research method uses classroom action research..The research subjects were 13 student.corsiiting 0f 5 bays and 8 girls.The data method can improve numeracy skill.Pre cycle of 55 % with is in the ceritena of not Developing.in the first cycle the action taken trough the project based learning (PJBL) method tho 65 % in the criretia of developing in accordanc with ecpectatino , and increased in the second cycle to 85 % on criteria ocorrding to expextation an very good development.Based on the results of this study ,it show that on increase in numeracy the skill of children aged 5-6 years with PJBL methods. Keywords: Cognitive Skills, Classifying citrus fruits, Classroom Action Research